Oral Photoprotection: Effective Agents and Potential Candidates - Parrado, Concepción; Philips, Neena; Gilaberte, Yolanda; Juarranz, Angeles; González, Salvador (Frontiers in Medicine, 2018)
Electromagnetic radiation in the ultraviolet, visible and infrared ranges produces biologic effects in humans. Where some of these effects are beneficial, others are harmful to the skin, particularly those stemming from ultraviolet radiation (UVR). Pharmacological photoprotection can be topical or systemic. Systemic photoprotection is often administered orally, complementing topical protection. New and classic oral agents (e.g., essential micronutrients as vitamins, minerals, polyphenols, carotenoids) are endowed with photoprotective and anti-photocarcinogenic properties. These substances bear the potential to increase systemic protection against the effects of electromagnetic radiation in the UV, visible, and infrared ranges. Protective mechanisms vary and include antioxidant, anti-inflammatory, and immunomodulatory effects. As such, they provide protection against UVR and prevent photo-induced carcinogenesis and aging. In this review, we present state of the art approaches regarding the photoprotective effects of vitamins and vitamin derivatives, dietary botanical and nonbotanical agents. A growing body of data supports the beneficial effects of oral photoprotection on the health of the skin. More studies will likely confirm and expand the positive impact of oral dietary botanicals as complementary measures for photoprotection.